1997
DOI: 10.1103/physrevlett.79.2069
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Tetrahedral Interstitial Er in Si

Abstract: We report on the lattice location of Er in Si using the emission channeling technique. The angular distribution of conversion electrons emitted by the decay chain 167 Tm ͑t 1͞2 9.25 d͒ ! 167m Er ͑2.27 s͒ was monitored with a position-sensitive detector following room temperature implantation and annealing up to 950 ± C. Our experiments give direct evidence that Er is stable on tetrahedral interstitial sites in float-zone Si. We also confirm that rare earth atoms strongly interact with oxygen, which finally le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 16 publications
0
58
0
Order By: Relevance
“…29 These calculations were performed for Er incorporated into pure silicon with no extra impurity present. Furthermore Wahl et al 30 have recently experimentally demonstrated, by the emission channeling technique, that Er is in a tetrahedral interstitial site in float zone Si. A value of xϭ0.35 would imply that the crystal-field ground state has a ⌫ 6 representation and a single sharp isotropic EPR spectrum with a g value of 6.8 would be predicted.…”
Section: A Effects Of Different O Concentrations On Epr and Pl Spectramentioning
confidence: 99%
“…29 These calculations were performed for Er incorporated into pure silicon with no extra impurity present. Furthermore Wahl et al 30 have recently experimentally demonstrated, by the emission channeling technique, that Er is in a tetrahedral interstitial site in float zone Si. A value of xϭ0.35 would imply that the crystal-field ground state has a ⌫ 6 representation and a single sharp isotropic EPR spectrum with a g value of 6.8 would be predicted.…”
Section: A Effects Of Different O Concentrations On Epr and Pl Spectramentioning
confidence: 99%
“…Knowledge of the microscopic structures of the rare earth impurities in semiconductor hosts is very important for fabricating efficient injection-type light emitting devices. To understand the microscopic structures, the electron spin resonance ͑ESR͒ measurements, [1][2][3][4][5][6][7] the extended x-ray absorption fine structure ͑EXAFS͒ measurements, 8,9 and the Rutherford backscattering ͑RBS͒ channeling measurements [10][11][12][13] have been performed on Er-doped GaAs, Er-doped Si, and Yb-doped InP.…”
Section: Introductionmentioning
confidence: 99%
“…Following implantation of 167 Tm with doses from 6×10 12 to 5×10 13 cm -2 and annealing at 600°C, we find the majority of 167m Er on near-tetrahedral interstitial (T) sites in both FZ and CZ Si [5,6]. For FZ Si, in-situ measurements at 900°C give direct evidence that 167m Er even resides on these sites at that temperature [7].…”
Section: Resultsmentioning
confidence: 97%
“…While the exact mechanisms of how O enhances the luminescence yield of Er are still a matter of debate, the binding of O to Er can be regarded as well-proven. As a complementary technique to EXAFS and TEM we use conversion electron emission channeling from the radioactive nucleus 167m Er in order to characterize the structural properties of Er in Si [5][6][7][8][9]. While EXAFS investigates the immediate neighbourhood of the Er atoms and TEM visualizes the crystalline quality on a nanoscale, emission channeling measures the position of the Er nucleus with respect to the lattice of a single crystal.…”
Section: Introductionmentioning
confidence: 99%